-10x+15=6x+3

Simple and best practice solution for -10x+15=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10x+15=6x+3 equation:


Simplifying
-10x + 15 = 6x + 3

Reorder the terms:
15 + -10x = 6x + 3

Reorder the terms:
15 + -10x = 3 + 6x

Solving
15 + -10x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
15 + -10x + -6x = 3 + 6x + -6x

Combine like terms: -10x + -6x = -16x
15 + -16x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
15 + -16x = 3 + 0
15 + -16x = 3

Add '-15' to each side of the equation.
15 + -15 + -16x = 3 + -15

Combine like terms: 15 + -15 = 0
0 + -16x = 3 + -15
-16x = 3 + -15

Combine like terms: 3 + -15 = -12
-16x = -12

Divide each side by '-16'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| 3(x+2)=1 | | (4v-7)(1-v)=0 | | 6q-1=-p+20 | | 5x+3x+4=-12 | | 7(z+4)=6z | | 12(x-3)=-6-6 | | 3x/5+7/2=x/10 | | 5y-9=6y-1 | | T/10=3/35 | | A=Ao/2n | | 3/4=w/18 | | 3(2x-5y)-2(x-3y)= | | 2(3+x)=19 | | -9(y-1)=-8y-6 | | 3/4=w/35 | | -7(-2y+4)-y=4(y-3)-1 | | y=0.95x+6 | | 22-13x=-8-2x-18x | | sen(x)+2cos(x)=1 | | 6x-8=5x+90 | | 3x-40=x-18 | | 5p-3p-30=-18 | | 4x+4=31-5x | | 8x-9+x=180 | | 2x-5+x=2 | | 3x+4=84-5x | | 3x+84=10x+14 | | 2x+17=45-2x | | =5.6e | | 6mn(m+1)= | | =5.6e+8 | | 4x+13=48-3x |

Equations solver categories